Filosofi Informasi Dalam Pemberdayaan Layanan Perpustakaan - Umar Falahul Alam (IAIN Ponorogo, 2014)
Abstract: The existence of the library indicates information services. The service shows two interrelated variables: the provider on the one hand and consumers on the other. Because of relation between service provider and customer satisfaction, then the service should be increased from time to time. Library services also needs to be improved. Increased library services must be appropriated by it’s responsibility to support education, teaching, research and community service. There is no doubt, that the library plays an important role in the process of education and teaching. The frst library becomes an intermediary between the users and their information needs. Second, the library can be an information provider on one side and can be consulted for the users in their academic activities. Third, the library can be a teacher who teaches the users the skills and strategies in managing, utilizing, and creating information. The role of the library likes this, is named empowerment of library services